Method for producing combustion ash with high silicon dioxide content and method for producing tetraalkoxysilane using combustion ash with high silicon dioxide content as raw material
By wet grinding and acid treating combustion ash, the method enhances the reactivity and purity of silicon dioxide, leading to improved yields of alkoxysilanes, addressing the limitations of existing technologies.
Patent Information
- Application Number
- JP2021062541
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-01
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-04-01
AI Technical Summary
Existing methods for producing combustion ash with high silicon dioxide content and improved reactivity are limited, resulting in suboptimal yields of alkoxysilanes due to the ash's low reactivity and high crystalline content.
A method involving wet grinding of combustion ash followed by acid treatment, which increases the specific surface area and reactivity of the ash, allowing for more efficient conversion of silicon dioxide into alkoxysilanes.
The method significantly improves the yield of alkoxysilanes by enhancing the reactivity and purity of the silicon dioxide in the combustion ash, achieving higher conversion rates compared to untreated ash or ash treated with acid alone.
Smart Images

Figure 0007662152000001 
Figure 0007662152000002 
Figure 0007662152000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing combustion ash with a high silicon dioxide content, and a method for producing tetraalkoxysilane using combustion ash with a high silicon dioxide content as a raw material. [Background technology]
[0002] In combustion furnaces such as coal-fired power plants, coal ash containing silicon dioxide is generated as coal is burned. Disposal of coal ash is costly, so effective use is required, and it is used as a cement admixture in the cement and concrete fields, as artificial lightweight aggregate in the civil engineering and construction fields, and as a fertilizer and snow melting agent in the agriculture, forestry and fisheries fields. The main component of coal ash is silicon dioxide, and therefore, the present inventors have developed a method for producing alkoxysilanes using silicon dioxide contained in coal ash from the viewpoint of reducing the volume of coal ash to facilitate disposal (Patent Documents 1 and 2). Coal ash has a high content of crystalline matter due to its thermal history in a combustion furnace, and is low in reactivity, so that the reaction rate from silicon dioxide to alkoxysilanes is not necessarily sufficient. Therefore, Patent Document 1 discloses a method for producing an organosilicon compound, which is characterized by including a step of reacting combustion ash containing silicon dioxide with an alcohol compound in the presence of at least one catalyst selected from the group consisting of alkali metal fluorides and ammonium fluoride to obtain alkoxysilanes. Patent Document 2 discloses a method for producing an organosilicon compound, which is characterized by including a grinding process step of wet-grinding combustion ash containing silicon dioxide together with a dispersion medium, and a reaction step of reacting the combustion ash after the wet grinding with an alcohol compound in the presence of a catalyst to obtain alkoxysilanes. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-196335 A [Patent Document 2] JP 2019-196336 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention aims to provide a method for producing combustion ash with a high content of silicon dioxide and improved reactivity. It is also an object of the present invention to provide a method for producing alkoxysilanes using the combustion ash with a high content of silicon dioxide obtained by the above-mentioned production method as a raw material. [Means for solving the problem]
[0005] As a result of extensive research aimed at solving the above problems, the inventors have discovered that by wet-pulverizing combustion ash containing silicon dioxide and then treating it with acid, or by wet-pulverizing combustion ash containing silicon dioxide in the presence of acid, the purity of silicon dioxide (SiO2) can be improved and the specific surface area can be increased at the same time, thereby completing the present invention. The present invention provides the following specific embodiments. [1] A grinding process for wet grinding the combustion ash containing silicon dioxide together with a dispersion medium; and an acid treatment step of treating the combustion ash after the wet grinding with an acid. [2] A method for producing combustion ash with a high silicon dioxide content, comprising a pulverization-acid treatment process in which combustion ash containing silicon dioxide is wet-pulverized in the presence of an acid. [3] The specific surface area of the combustion ash after the wet grinding is 30 m 2 / g or more. The method for producing combustion ash with a high silicon dioxide content according to [1]. [4] The method for producing combustion ash with a high silicon dioxide content according to any one of [1] to [3], wherein the acid is hydrochloric acid or nitric acid. [5] A method for producing alkoxysilanes, comprising a reaction step of reacting combustion ash with a high content of silicon dioxide, obtained by the method for producing combustion ash with a high content of silicon dioxide according to any one of [1] to [4], with an alcohol compound to produce alkoxysilanes. Effect of the Invention
[0006] According to the present invention, there is provided a method for producing combustion ash having a high content of silicon dioxide and having improved reactivity, and a method for producing alkoxysilanes using the combustion ash having a high content of silicon dioxide obtained by the above-mentioned production method as a raw material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] In explaining the details of the present invention, specific examples will be given. However, the present invention is not limited to the following contents as long as it does not deviate from the spirit of the present invention, and can be modified as appropriate.
[0008] 1. Manufacturing method of combustion ash with high silicon dioxide content The method for producing combustion ash with a high silicon dioxide content according to the first embodiment of the present invention is characterized by including a grinding process step of wet-grinding combustion ash containing silicon dioxide together with a dispersing medium, and an acid treatment process step of acid-treating the combustion ash after the wet grinding. Furthermore, the method for producing combustion ash with a high silicon dioxide content according to the second embodiment of the present invention is characterized by including a pulverization-acid treatment process in which combustion ash containing silicon dioxide is wet-pulverized in the presence of an acid. In addition, the high silicon dioxide content combustion ash in the first and second embodiments of the present invention has a silicon dioxide content of typically 70% by weight or more, preferably 72% by weight or more, more preferably 73% by weight or more, and even more preferably 74% by weight or more, and is typically 95% by weight or less.
[0009] In Patent Documents 1 and 2, the reaction rate is improved by improving the catalyst and pulverization method, but the maximum yield of tetraalkoxysilane (reaction rate of silicon dioxide) is 36.2%. Patent Document 2 also discloses that the yield of tetraalkoxysilane (reaction rate of silicon dioxide) was improved from 11% to 18% by treating combustion ash containing silicon dioxide with acid before wet pulverization. As a result of repeated investigations, the inventors have found that the purity of silicon dioxide (SiO2) is improved and the specific surface area is increased at the same time by wet-pulverizing combustion ash containing silicon dioxide and then treating it with an acid, or by pulverizing combustion ash containing silicon dioxide in the presence of an acid. Furthermore, they have found that the combustion ash obtained in this way has a higher reactivity and can improve the yield, for example, in the production of tetraalkoxysilane. The reason why the present invention has an effect is presumed to be as follows. As shown in the examples below, the acid treatment of fly ash alone does not improve the SiO2 purity much and is less effective. This is thought to be because the Si-O-Si structure, which is relatively resistant to acid conditions, contains components other than silica, such as aluminum and calcium, which are difficult to contact with acid. It is thought that the impurity components are exposed to the surface by pulverization and dissolve when they come into contact with acid, resulting in an improvement in the SiO2 purity. At the same time, if aluminum is contained in SiO2, the elution of the aluminum component causes the formation of pores or further collapse of particles, resulting in a significant increase in the specific surface area, which is thought to be one of the factors that improve reactivity. On the other hand, the specific surface area can be improved by grinding alone, but the aluminum components are not removed by grinding alone, and so there are units called [Si-O-Al-O-Si] in the skeleton (composite oxides of silicon and aluminum). It is presumed that the presence of this bond network results in low reactivity. Therefore, it is believed that the removal of aluminum components by acid treatment after grinding or by acid treatment simultaneously with grinding, combined with the improvement in SiO2 purity itself, contribute to the improvement of reactivity.
[0010] 1-1. Method for producing combustion ash with high silicon dioxide content according to the first embodiment (Crushing process) In the grinding process, the combustion ash containing silicon dioxide is wet-ground together with a dispersion medium using a mortar and pestle, a general grinding machine such as a ball mill, or the like. For example, when a planetary ball mill is used, the container and balls serving as the stirring medium used in the planetary ball mill apparatus may be made of materials such as stainless steel, agate, alumina, tungsten carbide, chromium steel, zirconia, silicon nitride, etc. Among these materials, zirconia, agate, and alumina are preferred, and zirconia is more preferred. The size of the vessel used in the planetary ball mill is not particularly limited, but is usually 10 to 1000 cm 3 The size of the ball is not particularly limited, but the diameter is about 2 to 20 mm. For example, the size of the container is 10 to 20 cm. 3 In the case of a container having a diameter of about 3 to 6 mm, the balls are preferably about 3 to 6 mm in diameter. From the viewpoint of reaction efficiency, the ball filling rate is preferably 20 to 50% by volume of the size of the container (container volume), and more preferably 25 to 40% by volume. A commercially available device can be used as the planetary ball mill device, and specific examples of preferred planetary ball mills include the Planetary Ball P-5 Classic Line (manufactured by Fritsch, Germany) and the Planetary Ball Mill P-6 Classic Line (manufactured by Fritsch, Germany). Examples of suitable ball mills include the Planetary Ball Mill P-7 (manufactured by Fritsch, Germany), and Planetary Ball Mill PM100 (manufactured by Verder Scientific, Germany). The combustion ash containing silicon dioxide is not particularly limited, but examples thereof include coal ash such as clinker ash and fly ash; soot remaining after burning plants such as rice husks, oats, and millet; etc., and coal ash is preferably used. As the coal ash, fly ash is preferable from the viewpoint of improving the yield when used in the production of alkoxysilanes.
[0011] The dispersion medium is not particularly limited as long as it can wet-pulverize the combustion ash containing silicon dioxide. Examples of the dispersion medium include various organic solvents such as alcohol compounds, ether compounds, and ester compounds. These organic solvents may be used alone or in combination of two or more. Among these, the dispersion medium is preferably an alcohol-based dispersion medium made of an alcohol compound. This is because the alcohol dispersion medium can act as a grinding aid that increases the fluidity of the combustion ash by appropriately alkoxylating the hydroxyl groups newly generated on the surface of the combustion ash containing silicon dioxide during grinding, thereby increasing the fluidity of the combustion ash and making the grinding more efficient.
[0012] In addition, the alcohol-based dispersion medium is preferably made of an alcohol compound having 1 to 5 carbon atoms. Examples of the alcohol-based dispersion medium having 1 to 5 carbon atoms include methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, s-butanol, t-butanol, and pentanol. Among these, methanol, ethanol, n-propanol, and i-propanol are preferred, and ethanol is more preferred. By using these alcohol-based dispersion media, even when the alcohol-based dispersion medium is used as the alcohol compound in the reaction step described below, it is possible to improve the reactivity between silicon dioxide and the alcohol compound, so that the silicon dioxide in the combustion ash can be efficiently converted into alkoxysilane.
[0013] The amount of the dispersion medium is not particularly limited as long as it can pulverize the combustion ash. For example, the amount of the dispersion medium is preferably 100 parts by mass or more, more preferably 200 parts by mass or more, and even more preferably 300 parts by mass or more, and is preferably 10,000 parts by mass or less, more preferably 5,000 parts by mass or less, and even more preferably 3,000 parts by mass or less, relative to 100 parts by mass of the combustion ash. This makes the combustion ash into a slurry during pulverization, so that the combustion ash can be efficiently pulverized.
[0014] The conditions of the wet grinding in the grinding process are not particularly limited as long as the combustion ash can have a desired specific surface area. The temperature of the wet grinding is, for example, 20°C or higher and 100°C or lower. The time of the wet grinding is, for example, 1 hour or higher and 24 hours or lower. When this process is carried out using a grinder, the grinder rotation speed is usually 50 rpm or higher and usually 1000 rpm or lower, preferably 500 rpm or lower. In the crushing process, the specific surface area of the combustion ash is reduced to 30 m 2 / g or more, and 2 / g or more is more preferable, and 50m 2 It is more preferable that the viscosity is 500m 2 / g or less, and 150m 2 / g or less is more preferable, and 90m 2 It is more preferable that the specific surface area of the combustion ash after wet pulverization is 30 m 2 When the specific surface area of the combustion ash is in a range suitable for reaction with the alcohol compound, it becomes possible to efficiently convert silicon dioxide in the combustion ash into alkoxysilane.
[0015] (Acid treatment process) The method for producing combustion ash according to the first embodiment of the present invention includes an acid treatment step in which the combustion ash after wet pulverization is treated with an acid. This acid treatment further improves the specific surface area of the combustion ash, so that the silicon dioxide in the combustion ash can be efficiently converted to alkoxysilane. Examples of acids used in the acid treatment include hydrochloric acid, sulfuric acid, and nitric acid. Among these, hydrochloric acid or nitric acid is preferred, and hydrochloric acid is more preferred. The concentration of the acid is not particularly limited, but is usually 1 mol / L or more, preferably 1.2 mol / L or more, more preferably 1.5 mol / L or more, and is usually 10.0 mol / L or less, preferably 6 mol / L or less, and more preferably 4.0 mol / L or less. The amount of acid used (the amount of the aqueous solution used in the case of an aqueous solution) is not particularly limited, and is usually 10 parts by mass or more, preferably 20 parts by mass or more, more preferably 30 parts by mass or more, per part by mass of combustion ash after the pulverization treatment, and is usually 10,000 parts by mass or less, preferably 5,000 parts by mass or less, more preferably 3,000 parts by mass or less.
[0016] The temperature and time of the acid treatment step are not particularly limited as long as the combustion ash can have a desired specific surface area. The temperature of the acid treatment is usually 25°C or higher, preferably 50°C or higher, and usually 100°C or lower, preferably 90°C or lower. The time of the acid treatment is usually 1 minute or more, preferably 30 minutes or more, more preferably 1 hour or more, and usually 24 hours or less, preferably 18 hours or less, more preferably 16 hours or less. The acid treatment can be carried out using a container with an acid-resistant surface, and may be carried out with stirring, and is preferably carried out with stirring. The combustion ash after the acid treatment is preferably washed with water and then dried. In the acid treatment process, the specific surface area of the combustion ash is increased to 50 m 2 / g or more, and 70m 2 / g or more is more preferable, and 90m 2 / g or more is more preferable, and 2 / g or less, and 2 / g or less is more preferable, and 300m 2 When the specific surface area of the silicon dioxide-rich combustion ash after the acid treatment is in the above-mentioned range, it is in a range suitable for reaction with an alcohol compound, so that the silicon dioxide in the combustion ash can be efficiently converted into an alkoxysilane. The specific surface area of the combustion ash is determined by the BET method using nitrogen gas adsorption measurements. The silicon dioxide content in the combustion ash is measured by X-ray fluorescence analysis using the fundamental parameter method.
[0017] 1-2. Method for producing combustion ash with high silicon dioxide content according to the second embodiment (Crushing-acid treatment process) The method for producing combustion ash with a high content of silicon dioxide according to the second embodiment of the present invention includes a pulverization-acid treatment step in which combustion ash containing silicon dioxide is wet-pulverized in the presence of an acid. That is, the pulverization and acid treatment of the combustion ash containing silicon dioxide are performed simultaneously. The grinding-acid treatment step can be carried out using a container with an acid-resistant surface, etc. For example, the combustion ash containing silicon dioxide is wet-ground in the presence of an acid using a mortar and pestle, a general grinding machine such as a ball mill, etc. For example, when a planetary ball mill is used, the planetary ball mill may be one having an acid-resistant surface among those described in the explanation of the grinding process in "1-1. Method for producing combustion ash with a high silicon dioxide content according to the first embodiment," and is preferably made of a material such as alumina or zirconia. The combustion ash containing silicon dioxide and the acid are the same as those in the first embodiment. In this embodiment, the pulverization is performed in acid, so that the combustion ash containing silicon dioxide can be wet-pulverized without using a dispersion medium such as an organic solvent. Water, an alcohol compound, or the like can also be used as the dispersion medium. When water is used as the dispersion medium, the concentration of the acid is calculated including the water as the dispersion medium. The amount of acid used is not particularly limited as long as it can pulverize the combustion ash, and is usually 100 parts by mass or more, preferably 200 parts by mass or more, more preferably 300 parts by mass or more, and is usually 10,000 parts by mass or less, preferably 5,000 parts by mass or less, more preferably 3,000 parts by mass or less, relative to 100 parts by mass of the combustion ash. This makes the combustion ash into a slurry during pulverization, allowing the combustion ash to be efficiently pulverized. The conditions for the pulverization-acid treatment step are not particularly limited as long as the combustion ash can have a desired specific surface area. The temperature for the pulverization-acid treatment step is usually 1° C. or higher and 100° C. or lower, and preferably room temperature. In this specification, room temperature means 1° C. to 30° C. The time for the acid treatment is usually 30 minutes or longer, preferably 1 hour or longer, and usually 240 hours or shorter, preferably 200 hours or shorter, and more preferably 180 hours or shorter. When this step is performed using a pulverizer, the rotation speed of the pulverizer is usually 50 rpm or higher, and usually 1000 rpm or lower, and preferably 500 rpm or lower. The combustion ash after the pulverization and acid treatment is preferably washed with water and then dried. In the crushing and acid treatment process, the specific surface area of the combustion ash is increased to 50 m 2 / g or more, and 70m 2 / g or more is more preferable, and 90m 2 / g or more is more preferable, and 2 / g or less, and 2 / g or less is more preferable, and 300m 2 When the specific surface area of the silicon dioxide-rich combustion ash obtained by the pulverization-acid treatment is within the above-mentioned range, it is suitable for reaction with an alcohol compound, and therefore it is possible to efficiently convert the silicon dioxide in the combustion ash into an alkoxysilane. The method for measuring the specific surface area of the combustion ash and the method for measuring the silicon dioxide content in the combustion ash are the same as those in "1-1. Manufacturing method for combustion ash with high silicon dioxide content according to the first embodiment".
[0018] 2. Method for producing alkoxysilane A method for producing alkoxysilanes according to one embodiment of the present invention includes a reaction step of producing alkoxysilanes by reacting the silicon dioxide-rich combustion ash obtained by the above-mentioned method for producing silicon dioxide-rich combustion ash with an alcohol compound. In the reaction step, as shown in the following formula (1), the silicon dioxide-rich combustion ash after the pulverization treatment is reacted with an alcohol compound in the presence of a catalyst to obtain an alkoxysilane. Note that, in the following formula (1), an example is shown in which four molecules of an alcohol compound are reacted with silicon dioxide, but the number of molecules of the alcohol compound reacted with silicon dioxide can be appropriately changed depending on the alcohol compound used and the reaction conditions. For example, in the case of the alkoxysilane of this embodiment, The method for producing an alkoxysilane may involve reacting silicon dioxide with four molecules of an alcohol compound to produce a tetraalkoxysilane, or it may involve reacting silicon dioxide with three molecules of an alcohol compound to produce a trialkoxysilane, or it may involve reacting silicon dioxide with two molecules of an alcohol compound to produce a dialkoxysilane, or it may involve reacting silicon dioxide with one molecule of an alcohol compound to produce a monoalkoxysilane. [ka]
[0019] The alcohol compound is used as a reaction component and a solvent that reacts with silicon dioxide. There is no particular limitation on the alcohol compound as long as it reacts with silicon dioxide to obtain alkoxysilane. The alcohol compound is preferably an alcohol compound having 1 to 5 carbon atoms. This further improves the reaction rate between the alcohol compound and the catalyst, making it possible to further improve the reaction rate from silicon dioxide contained in the combustion ash with a high silicon dioxide content to alkoxysilane. Examples of the alcohol compound having 1 to 5 carbon atoms include methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, s-butanol, t-butanol, and pentanol. Among these, methanol, ethanol, n-propanol, or i-propanol is preferred, and ethanol is more preferred.
[0020] The amount of the alcohol compound used, from the viewpoint of improving the reaction rate with silicon dioxide in the silicon dioxide-rich combustion ash, is preferably 100 parts by mass or more, more preferably 500 parts by mass or more, and even more preferably 1,000 parts by mass or more, relative to 100 parts by mass of silicon dioxide in the silicon dioxide-rich combustion ash, and is preferably 100,000 parts by mass or less, more preferably 50,000 parts by mass or less, and even more preferably 10,000 parts by mass or less.
[0021] The catalyst is not particularly limited as long as it can produce an alkoxysilane from silicon dioxide and an alcohol compound, and various basic substances can be used. For example, various basic compounds such as potassium hydroxide, calcium carbonate, ammonium fluoride, potassium fluoride, cesium fluoride, and sodium fluoride can be used as the catalyst.
[0022] The amount of catalyst used is preferably 10 mol% or more, more preferably 20 mol% or more, even more preferably 30 mol% or more, even more preferably 50 mol% or more, and is preferably 100 mol% or less, more preferably 80 mol% or less, relative to the silicon dioxide in the combustion ash, from the viewpoint of improving the reaction rate between the silicon dioxide contained in the combustion ash with a high silicon dioxide content and the alcohol compound.
[0023] In addition, in the method for producing alkoxysilane, the reaction may be carried out using an additive other than the catalyst in the reaction step. For example, such an additive may be a dehydrating agent that removes water from the reaction system. This allows the water generated in the system by the progress of the reaction of the above formula (1) to be removed, thereby further improving the reaction rate of silicon dioxide. As the dehydrating agent, various molecular sieves are preferable, and molecular sieve 3A is more preferable. The amount of the dehydrating agent used is preferably, for example, 100 parts by mass or more and 10,000 parts by mass or less with respect to 100 parts by mass of silicon dioxide contained in the combustion ash with a high silicon dioxide content, from the viewpoint of improving the reactivity between the silicon dioxide contained in the combustion ash with a high silicon dioxide content and the alcohol compound.
[0024] The reaction temperature in the reaction step is not particularly limited as long as it is a temperature at which alkoxysilane can be obtained. The reaction temperature can be determined, for example, based on the reaction rate of silicon dioxide in the combustion ash with a high silicon dioxide content. From the viewpoint of improving the reaction rate of silicon dioxide in the combustion ash with a high silicon dioxide content, the reaction temperature is preferably 150° C. or higher, more preferably 210° C. or higher, and is preferably 300° C. or lower, more preferably 270° C. or lower. The reaction time in the reaction step is preferably, for example, 1 hour or longer and shorter than 50 hours, from the viewpoint of improving the reaction rate of silicon dioxide in the combustion ash with a high silicon dioxide content. EXAMPLES
[0025] The present invention will be described in more detail below with reference to examples, but the examples can be modified as appropriate without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be construed as being limited to the specific examples shown below.
[0026] [Example 1] BET specific surface area 2.2m 2 20 g of fly ash (SiO2 content 65.5%) with a BET specific surface area of 33.3 m was mixed with 65 g of ethanol and wet-ground for 3 hours at 300 rpm using a ball mill (model number: PM100, manufactured by Verder Scientific) with zirconia balls (mean spherical diameter 1 mm). The ethanol was then removed by drying, resulting in a powder with a BET specific surface area of 33.3 m. 2 / g of fly ash was obtained. 3.0 g of the obtained fly ash was mixed with 100 g of 2 mol / L hydrochloric acid and heated and stirred at 80 °C for 2 hours for acid treatment. After the acid treatment, the fly ash was collected by filtration, washed with water, and then dried. After this pulverization and acid treatment process, the BET specific surface area of the fly ash before being used in the tetraethoxysilane synthesis reaction was 98.9 m 2 / g, and the SiO2 content was 73%. A 100 mL SUS portable reactor (Taiatsu Glass Co., Ltd.) containing 90 g of molecular sieve 3A (Merck: 2 mm bead type) was connected to the top of a 200 mL SUS316 autoclave (Nitto Koatsu Co., Ltd.) equipped with a mechanical stirrer via a 4.6 mm inner diameter SUS316 tube. Constant temperature water was circulated outside the portable reactor to maintain the temperature of the molecular sieve inside the portable reactor at 60°C. In the autoclave, 90 g of ethanol and the fly ash obtained by the wet grinding and acid treatment were added so that the amount of SiO2 was 0.9 g. Furthermore, potassium hydroxide was added as a catalyst at 10 mol% relative to the SiO2 in the fly ash, and argon gas was filled from a cylinder at a temperature of 25°C so that the autoclave was at 0.75 MPa at the pressure indicated by a pressure gauge (Swagelok FST PGC-50M-MG10), and the autoclave was held while stirring for 10 minutes and sealed. After that, the inside of the autoclave was reacted at 240°C for 15 hours while stirring at 500 rpm. The yield of tetraethoxysilane based on (SiO2) was 55%. The results are shown in Table 1 below.
[0027] [Example 2] Tetraethoxysilane was synthesized in the same manner as in Example 1, except that the conditions for wet pulverization in a ball mill were changed to 300 rpm and 6 hours compared to the conditions in Example 1. The results are shown in Table 1.
[0028] [Example 3] Tetraethoxysilane was synthesized in the same manner as in Example 1, except that the conditions for wet grinding in a ball mill were changed to 500 rpm for 6 hours and the concentration of hydrochloric acid used in the acid treatment was changed to 4 mol / L. The results are shown in Table 1.
[0029] [Comparative Example 1] Tetraethoxysilane was synthesized in the same manner as in Example 1, except that the fly ash was left untreated without being crushed or treated with acid. The results are shown in Table 1.
[0030] [Comparative Example 2] Tetraethoxysilane was synthesized in the same manner as in Example 1, except that the conditions of wet grinding in a ball mill were changed to 500 rpm for 6 hours and the treatment with hydrochloric acid was not performed. The results are shown in Table 1.
[0031] [Comparative Example 3] Tetraethoxysilane was synthesized in the same manner as in Example 1, except that wet pulverization with a ball mill was not performed and only acid treatment was performed by changing the concentration of hydrochloric acid used in the acid treatment to 4 mol / L. The results are shown in Table 1.
[0032] [Comparative Example 4] The procedure for treating the fly ash was changed to first acid treatment and then pulverization, and the wet pulverization conditions in the ball mill were changed to 500 rpm, 6 hours, and the concentration of hydrochloric acid used in the acid treatment was changed to 4 mol / L, so that only the acid treatment was performed. Tetraethoxysilane was synthesized in the same manner as in Example 1. The results are shown in Table 1.
[0033] [Example 4] BET specific surface area 2.2m 2 3 g of fly ash (SiO2 content 65.5%) with 0.1 g / g was mixed with 30 g of 2 mol / L hydrochloric acid, and added to a mortar (φ130 mm) of a magnetic mortar set manufactured by AS ONE Corporation. The magnetic stirrer was set to rotate at 100 rpm, and the magnetic pestle (φ55 mm) was rotated, and the mixture was simultaneously ground in the mortar and treated with acid for 168 hours at room temperature (25°C). After this simultaneous grinding and acid treatment, the fly ash was recovered by filtration, washed with water, and then dried. After this simultaneous grinding and acid treatment process, the BET specific surface area of the fly ash before use in the tetraethoxysilane synthesis reaction was 74.5 m 2 / g, and the SiO2 content was 71.8%. Using this fly ash, tetraethoxysilane was synthesized under the same conditions as in Example 1. The results are shown in Table 2.
[0034] [Comparative Example 5] Tetraethoxysilane was synthesized in the same manner as in Example 4, except that the mortar grinding was carried out in water and no acid treatment was carried out. The results are shown in Table 2.
[0035] [Table 1]
[0036] [Table 2]
[0037] A comparison between Comparative Example 1 and Comparative Example 2 shows that, although an increase in the specific surface area was observed when only the grinding treatment was performed, the yield of alkoxysilane was not significantly improved compared to the untreated case. The decrease in the purity of silicon dioxide was due to the inclusion of zirconia ball components used in the grinding. In addition, a comparison between Comparative Example 3 and Comparative Example 1 shows that the specific surface area hardly changes when only the acid treatment is performed. The purity of silicon dioxide is slightly improved, but the yield of alkoxysilane is almost the same as that of the untreated case. From Comparative Example 4, when the acid treatment was performed first and then the pulverization treatment was performed, the specific surface area was the same as that of the pulverization alone, and the purity of silicon dioxide did not improve. Although the alkoxysilane yield was improved to a certain extent compared to the untreated case, the difference was not significant. From Examples 1 to 3, it can be seen that by wet-pulverizing the combustion ash containing silicon dioxide and then treating it with acid, the purity of silicon dioxide (SiO2) is improved and a high-silicon dioxide content combustion ash with an increased specific surface area can be obtained. In addition, it can be seen that by reacting the combustion ash containing silicon dioxide with alcohol as a raw material, alkoxysilane can be obtained in a much higher yield than when untreated combustion ash, combustion ash that was not subjected to either crushing or acid treatment (Comparative Examples 1 to 3), or combustion ash obtained by wet-pulverizing after acid treatment was used as a raw material (Comparative Example 4). Also, as can be seen from Table 2, by simultaneously carrying out pulverization and acid treatment, the purity of silicon dioxide (SiO2) was improved, and a high-silicon dioxide content combustion ash with an increased specific surface area was obtained. Furthermore, alkoxysilane was obtained in high yield using the high-silicon dioxide content combustion ash as a raw material. The yield of Example 4 was improved even compared to Comparative Example 4, in which wet pulverization was carried out after acid treatment.
[0038] From the above results, the reason why the present invention exhibits its effects is presumed to be as follows. Only acid treatment of fly ash does not improve SiO2 purity much and is less effective. This is thought to be because the Si-O-Si structure, which is relatively resistant to acid conditions, contains components other than silica, such as aluminum and calcium, which are difficult to contact with acid. It is thought that the impurity components are exposed to the surface by crushing and dissolve when they come into contact with acid, improving the SiO2 purity. At the same time, the elution of aluminum components causes the formation of pores or further collapse of particles, resulting in a significant increase in the specific surface area, which is thought to be one of the factors that improve the alkoxysilane yield. On the other hand, the specific surface area can be improved by crushing alone, but the improvement in alkoxysilane yield is limited. This is because the aluminum component is not removed by crushing alone, and there is a unit called [Si-O-Al-O-Si] in the skeleton (a composite oxide of silicon and aluminum). It is speculated that this is because this bond network cannot be effectively cut by the catalyst. Therefore, the removal of aluminum components by acid treatment after crushing or by acid treatment at the same time as crushing, and the improvement in SiO2 purity, are also thought to contribute to the high yield with the catalyst. [Industrial Applicability]
[0039] According to the present invention, it is possible to obtain a high-silicon dioxide content combustion ash with improved reactivity from unused combustion ash, and the combustion ash can be effectively utilized. In addition, it is possible to obtain alkoxysilane from the high-silicon dioxide content combustion ash obtained by the production method, which is very useful.
Claims
1. A process for producing combustion ash with a high content of silicon dioxide by a crushing process step of wet-crushing combustion ash containing silicon dioxide together with a dispersing medium, and an acid treatment process step of treating the combustion ash after the wet-crushing with an acid; and a reaction step of reacting the combustion ash with a high silicon dioxide content with an alcohol compound to produce an alkoxysilane.
2. A process for producing combustion ash with a high content of silicon dioxide by a crushing-acid treatment process in which combustion ash containing silicon dioxide is wet-crushed in the presence of an acid; and a reaction step of reacting the combustion ash with a high silicon dioxide content with an alcohol compound to produce an alkoxysilane.
3. The method for producing alkoxysilanes according to claim 1, wherein the specific surface area of the combustion ash after the wet grinding is 30 m 2 / g or more.
4. The method for producing alkoxysilanes according to claim 1, wherein the acid is hydrochloric acid or nitric acid.
Citation Information
Patent Citations
Filler for papermaking
JP2010236158A
Method of producing tetraalkoxysilane
JP2014051455A
Method for producing organosilicon compound
JP2019196335A
Method for producing organosilicon compound
JP2019196336A